Effect of Suctioning to Oxygen Saturation Improvement towards ICU Patients in Prof. Dr. W. Z. Johannes Regional Public Hospital Kupang - Anggreni, Fince Trisna; Muskananfola, Istha Leanni; Yudowaluyo, Akto (RSUP Dr. Kariadi, 2023)
BACKGROUND: Treated ICU patients may experience consciousness deterioration which leads to loss of cough response and increase of saliva and secretions production which blocks the airway. Therefore, patients need to receive suctioning or mucus suctioning to clear the airway. The success of such procedure can be supervised by measuring the patient's oxygen saturation level before and after the procedure. AIMS: The objection of this research was to analyze the effect of suctioning to oxygen saturation improvement towards ICU patients in Prof. Dr. W. Z. Johannes Regional Public Hospital Kupang. METHOD: The research was conducted from November to December 2022 in a quantitative form with a pre-experimental layout and one-group pre-posttest design. It involved 30 respondents with accidental sampling technique. The instruments used were suction observation sheets and the oximeter. The gained data were then analyzed using SPSS with the Mc Nemar test. RESULT: The results showed that the average value of the patient’s oxygen saturation pre-suctioning was 93.73% whilst post-suctioning was 96.23%. The statistical test results show the value of ρ = 0.002, which means that there is an effect of suctioning to oxygen saturation improvement towards ICU patients in Prof. Dr. W. Z. Johannes Regional Public Hospital Kupang. CONCLUSION: Suctioning has an effect to improve the oxygen saturation towards ICU patients in Prof. Dr. W. Z. Johannes Hospital Regional Public Hospital Kupang.